1. Factor each of the following completely. Look carefully at the structure of each quadratic function and consider the best way to factor. Is there a GCF? Is it an example of a special case? SHOW YOUR WORK

1 Factor each of the following completely Look carefully at the structure of each quadratic function and consider the best way to factor Is there a GCF Is it an class=

Respuesta :

Answer: 1) (x - 7)(x - 8)

               2) 2x(2x-7)(x + 2)

               3) (4x + 7)²

               4) (9ab² - c³)(9ab² + c³)

Step-by-step explanation:

1) x² - 15x + 56  → use standard form for factoring

                    ∧

                -7 + -8 = -15

  (x - 7) (x - 8)

************************************

2) 4x³ - 6x² - 28x      → factor out the GCF (2x)

2x(2x² - 3x - 14)         → factor using grouping

2x[2x² + 4x    - 7x - 14]    

2x[ 2x(x + 2)   -7(x + 2)]

2x(2x - 7)(x + 2)

*************************************

3) 16x² + 56x + 49     → this is the sum of squares

√(16x²) = 4x      √(49) = 7

              (4x + 7)²

******************************************************

4) 81a²b⁴ - c⁶          → this is the difference of squares

√(81a²b⁴) = 9ab²       √(c⁶) = c³

       (9ab² - c³)(9ab² + c³)

   

The required factor of x² - 15x + 56 is (x-7)(x-8)

The factor of 4x³ - 6x² - 28x is 2x(x-7)(2x+4)

The factor of 16² + 56x + 49 is (4x+7)(4x+7) = (4x+7)²

The factor of [tex]81a^{2}b^{4} - c^{6}\\[/tex] is (9ab² + c³)(9ab² - c³)

What is a factor?

A factor is a number that divides another number, leaving no remainder.

How to factor the expression in part I?

The given expression is

x² - 15x + 56

=x² - 7x - 8x + 56

= x(x-7) -8(x-7)

=(x-7)(x-8)

This is actually the standard way of factorization.

The required factor of x² - 15x + 56 is (x-7)(x-8)

How to factor the expression in part II?

The given expression is

4x³ - 6x² - 28x

=2x(2x² - 3x - 14)

=2x(2x² - 7x + 4x - 14)

=2x{2x(x - 7) + 4(x - 7)}

=2x(x-7)(2x+4)

  • Here the GCF is 2x

The factor of 4x³ - 6x² - 28x is 2x(x-7)(2x+4)

How to factor the expression in part III?

The given expression is

16² + 56x + 49

=16x² + 28x + 28x + 49

=4x(4x +7) + 7(4x + 7)

=(4x+7)(4x + 7)

=(4x+7)²

How to factor the expression in part IV?

The given expression is

[tex]81a^{2}b^{4} - c^{6}\\[/tex]

=(9ab²)² -(c³)²

  • We know that a² - b² can be written as (a+b)(a-b)

=(9ab² + c³)(9ab² - c³)

∴ The factor of [tex]81a^{2}b^{4} - c^{6}\\[/tex] is (9ab² + c³)(9ab² - c³)

Find more about "Factorization" here: https://brainly.com/question/25829061

#SPJ2

ACCESS MORE